Political Public Sphere and Mass Media: Critical Perspective - Fahrudin, Dedi; Rosyidin, Iding; Hosen, Nadirsyah (UIN Syarif Hidayatullah Jakarta, 2024)
Abstract. This paper aims to explain how political public sphere occurs in Republika media. Mass media as a public sphere ideally provides space for audiences to get balanced information and news related to developing political issues. Not being an apartus of power or entrepreneurs, but bridging public interests. This study uses qualitative research with a critical paradigm. The findings of this study are that Republika provides political public sphere for various political party backgrounds, news for Islamic and nationalist based parties are given the same space. Mass media as a public sphere is often used by rulers and businessmen for their political interests. Journalists as professional journalists can interact directly with politicians, with the limitation of not being allowed to led to the political publicity of the former owner of the Mahaka Group who became Minister of BUMN of the Republic of Indonesia. Keywords: Mass media, republika, public sphere, politics. Abstrak. Tulisan ini bertujuan untuk menjelaskan bagaimana ruang publik politik yang terjadi di media Republika. Media massa sebagai ruang publik idealnya memberikan ruang bagi khalayak untuk mendapatkan informasi dan berita yang seimbang terkait isu-isu politik yang berkembang. Tidak menjadi apartus kekuasaan maupun pengusaha, namun menjembatani kepentingan-kepentingan publik. Kajian ini menggunakan penelitian kualitatif dengan paradigma kritis. Temuan penelitian ini Republika memberikan ruang publik politik bagi berbagai latar belakang partai politik pemberitaan untuk partai berbasis islam maupun nasionalis diberikan ruang yang sama. Media massa sebagai ruang publik kerap digunakan oleh penguasa dan pengusaha untuk kepentingan politik mereka. Wartawan sebagai jurnalis profesional dapat berinteraksi langsung dengan politisi, dengan batasan tidak boleh masuk dalam struktur partai. Disisi lain ditemukan adanya pemberitaan yang mengarah kepada publisitas politik mantan pemilik Mahaka Grup yang menjadi Menteri BUMN Republik Indonesia. Kata Kunci: Media masa, republika, ruang publik, politik.